Financial Feasibility Analysis of the Beef Cattle Fattening Business - Mayulu, Hamdi; Puteri, Sarah Shevi Annisa; Christiyanto, Marry; Rorimpandey, Boyke (Jurnal Ilmu-Ilmu Peternakan, 2024)
Financial analysis is an activity of assessing and determining rupiah units on aspects that are considered feasible from decisions made in the business analysis stage, and the results of the analysis are used as basic parameters in determining the feasibility of a business. The objective of this research was to determine the financial feasibility of the beef cattle fattening business in Balikpapan city. The study employed a survey method within the North Balikpapan subdistrict, in which 40 respondents were selected through purposive sampling. Criteria for respondents included ownership of at least two beef cattle with a rearing period exceeding one year. The financial feasibility analysis used several key indicators, including the break event point (BEP), net present value (NPV), benefit cost ratio (B/C ratio), internal rate of return (IRR), and payback period (PP). Based on the study calculations, the BEP was IDR 9.676.911; NPV (9.15%) was IDR 1.017.779.514; NPV (14.15%) was IDR 952.403.118; B/C ratio was 2.7; IRR was 87%; and PP was 0.37 years. According to these results, it could be concluded that the beef cattle business in the North Balikpapan subdistrict, Balikpapan city, was feasible.